2015
DOI: 10.1097/mib.0000000000000446
|View full text |Cite
|
Sign up to set email alerts
|

Use of Humanized Mice to Study the Pathogenesis of Autoimmune and Inflammatory Diseases

Abstract: Animal models of disease have been used extensively by the research community for the past several decades to better understand the pathogenesis of different diseases as well as assess the efficacy and toxicity of different therapeutic agents. Retrospective analyses of numerous preclinical intervention studies using mouse models of acute and chronic inflammatory diseases reveal a generalized failure to translate promising interventions or therapeutics into clinically-effective treatments in patients. Although … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 217 publications
(397 reference statements)
0
34
0
Order By: Relevance
“…These inventions cascaded into a series of immunodeficient mice and their variants (BRG, NOG, NRG) (Ali et al 2012; Grover et al 2017; Ishikawa et al 2005; Katano et al 2014; Koboziev et al 2015; Shultz et al 2005) being innovated which enabled in-depth analysis in research areas, such as human hematopoiesis (Rongvaux et al 2011; Yong et al 2016), innate and adaptive immunity (Brehm et al 2010; Pearson et al 2008), autoimmunity (Gunawan et al 2017; Viehmann Milam et al 2014), infectious disease (Keng et al 2015; Lüdtke et al 2015; Wege et al 2012), cancer biology (Chang et al 2015; Her et al 2017; Morton et al 2016), and GvHD (King et al 2008; Kirkiles-Smith et al 2009; Zhao et al 2015), in-turn, facilitating the development of therapeutic agents and novel vaccines. An overview of genotypic and physiological characteristics of each model is outlined in Tables 1 and 2.…”
Section: Evolving History Of Humanized Micementioning
confidence: 99%
“…These inventions cascaded into a series of immunodeficient mice and their variants (BRG, NOG, NRG) (Ali et al 2012; Grover et al 2017; Ishikawa et al 2005; Katano et al 2014; Koboziev et al 2015; Shultz et al 2005) being innovated which enabled in-depth analysis in research areas, such as human hematopoiesis (Rongvaux et al 2011; Yong et al 2016), innate and adaptive immunity (Brehm et al 2010; Pearson et al 2008), autoimmunity (Gunawan et al 2017; Viehmann Milam et al 2014), infectious disease (Keng et al 2015; Lüdtke et al 2015; Wege et al 2012), cancer biology (Chang et al 2015; Her et al 2017; Morton et al 2016), and GvHD (King et al 2008; Kirkiles-Smith et al 2009; Zhao et al 2015), in-turn, facilitating the development of therapeutic agents and novel vaccines. An overview of genotypic and physiological characteristics of each model is outlined in Tables 1 and 2.…”
Section: Evolving History Of Humanized Micementioning
confidence: 99%
“…Human MC producing humice that have so far been described are based on a NOD‐scid IL2rg null SCF/GM‐CSF/IL‐3 (NSG‐SGM3) strain of mice engrafted with human umbilical cord blood or thymus, liver, and hematopoietic stem cells and which constitutively express GM‐CSF and IL‐3 have been reported . However, long‐term exposure and constitutive expression of human cytokines in humice can be challenging as non‐physiological effects are sometimes observed, including deleterious effects on the human stem cell compartments, and progressive anaemia and polarization of the immune system . Therefore, in our model, we performed a hydrodynamic gene delivery of human cytokines into humice, and found that we could markedly enhance the reconstitution and function of human immune cells subsets, without any undesirable side effects .…”
Section: Discussionmentioning
confidence: 99%
“…The development of peripheral lymph nodes and gut-associated lymphoid tissue (GALT) in the present humanized immune system mice is imperfect with defective formation of important substructures such as the germinal center. Efforts to address these problems are being made to reproduce the structure and function of human immune system more faithfully (reviewed in [Koboziev et al, 2015;Theocharides, Rongvaux, Fritsch, Flavell, & Manz, 2016]).…”
Section: Humanized Nervous System Micementioning
confidence: 99%